An Investigation on Analytical Techniques and Statistical Design for Tertiary Treatment of Secondary Wastewater using Zetag-4120 Coagulant - Singh P.; Pal M.K.; Dikshit P.K.S.; Banerjee G. (My University, 2025)
The primary and secondary treatments of wastewaters are important not only for the removal of pollutants but also for the use of treated water. The latter involves the use of suitable coagulants at their optimal dosages. The present study was carried out to identify the most suitable coagulant for tertiary treatment and its optimal dosage to achieve the maximum removal of total suspended solids (TSS) and biological oxygen demand (BOD). In the study, we used six coagulants (alum, ferric chloride, poly-aluminium chloride (PAC), Zetag-4120, Mecafloc-25 and Rothfloc-27) and found that Zetag-4120 is cost-efficient coagulant. We arrived at this conclusion based on several experiments performed using varying coagulant dosages. Furthermore, the regression prediction models for BOD and TSS removal for coagulant Zetag-4120 have been generated using statistical models and validated by calculating Rz value, F-test and lack-of-fit test using ANOVA. Analysis suggests the optimal dosage, initial wastewater pH and settling time to be 1.86 mg/L, 6.73 and 89.12 min, respectively. Furthermore, BOD and TSS removal efficiency values were 50.0% and 92.4%, respectively. The treated wastewater has BOD and TSS equal to 12.27 and 5.66 mg/L, respectively, conforming to the standard for re-usability of treated water in unrestricted irrigation. © 2024 - Kalpana Corporation.